Averaging of fuzzy systems - Perestyuk, N. A.; Skripnik, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We develop the ideas of the method of averaging for some classes of fuzzy systems (fuzzy differential equations with delay, fuzzy differential equations with pulsed action, fuzzy integral equations, fuzzy differential inclusions and differential inclusions with fuzzy right-hand sides without and with pulsed action).